Melasma: a clinico-epidemiological study in the highland Himalayan region of Kashmir - Fatima, Tabasum; Rather, Shameem A. (International Journal of Research in Dermatology, 2025)
Background: Melasma is an acquired dyschromia present mostly on the sun-exposed areas of the skin. The etiology for melasma is not clear, various factors like genetic or hormonal influences the cause. The aim was to understand the demographical distribution and epidemiological pattern of hyper pigmentation in melasma patients. Methods: A total of 36 patients participated in the present study at the OPD of Regional Research Institute of Unani Medicine, Srinagar, Kashmir for a period of one year. Results: In the present study, the mean age of patients with melasma was found to be 30.75±6.74 years, with the age distribution and age of onset ranging between 26 and 36 years. A female preponderance was observed, comprising 29 females and 7 males. Out of the total 36 patients, 21 were married, while 15 were unmarried. The maximum numbers of participants were housewives, and the majority belonged to the upper middle class. Furthermore, 10 patients reported a family history of melasma, whereas 26 patients had no such history. Conclusions: The present observations demonstrate that the melasma has female predominant, affecting reproductive age group mostly found in upper middle class and housewives.